The Role of Managers in R&D Organizational Networks. Are They Knowledge Workers or Bureaucrats? (School of Business and Management Institut Teknologi Bandung, 2022)
Abstract. In today’s competition-driven world, competitive advantage is the only way for an organization to survive. There are various ways to gain a competitive edge through the application of knowledge, technology, and science. Indonesian public research and development (R&D) faces numerous challenges, one of which is researchers’ low productivity in terms of international journal publications. To boost research productivity and performance, efforts must be made to streamline knowledge flows within public R&D institutions. Additionally, data from dynamic information flows in networks can be used to evaluate bureaucratic effectiveness and identify potential knowledge talents or actors within R&D organizations. The purpose of this study is to determine the role of managers at all levels in a public R&D organization in coordinating information flow through knowledge networks and bureaucratic relationships. The social network analysis (SNA) technique was used to map managers’ role in aligning knowledge flows in an Indonesian public R&D organization. Individuals were classified according to their type and centrality in the network, and network metrics such as “degree of centrality,” “eigenvector centrality,” and “clustering coefficient” were determined. It was found that the organization has some issues with knowledge flows and power distribution. The two distinct knowledge flow patterns, one for knowledge-seeking and the other for administrative knowledge, do not appear to be synchronized. The director of the R&D center is assumed to be less influential than the top manager in terms of knowledge and bureaucratic influence. At the managerial level, clique tendency is lower, while it is higher at the nonmanagerial level. Such centralization and cliques are dangerous because managing knowledge cannot be handled by a single person in a knowledge-intensive organization such as an R&D institution. Additionally, it was discovered that middle managers are critical for knowledge-seeking purposes, whereas administrative managers dominate the bureaucratic role. The research implications are dependent on deciphering the complexities of knowledge flows among employees and the variables that influence the knowledge-transfer process within an organization. This issue will exacerbate the problem by decreasing productivity and increasing reliance on a small number of people. Additional research is required to generalize the findings to other Indonesian R&D institutions.Keywords: Bureaucracy, knowledge management, social network analysis